2022
DOI: 10.5194/acp-2022-483
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Concurrent photochemical whitening and darkening of ambient brown carbon

Abstract: Abstract. The light-absorbing organic aerosol (OA), known as brown carbon (BrC), has important radiative impacts, however its sources and evolution after emission remain to be elucidated. In this study, the light absorption at multiple wavelengths, mass spectra of OA and microphysical properties of black carbon (BC) were characterized at a typical sub-urban environment in Beijing. The absorption of BC is constrained by its size distribution and mixing state, being subtracted from total absorption to obtain the… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…This hypothesis probably explains the higher MAEWS-BrC-365 values obtained during late night and morning time except afternoon, which recorded the greatest solar flux (Figure 1b). During afternoon time, a recent study 25 suggested that photochemical oxidation can cause concurrent oxygenation (bleaching) of existing BrC chromophores and formation of nitrogen containing BrC chromophores. Our observations during afternoon are supportive to this hypothesis that WS-BrC bleaching dominates any absorption enhancement whatsoever due to formation of nitrogen containing chromophores during afternoon resulting overall decrease in MAEWS-BrC-365.…”
Section: Diurnal Variability Of Ws-brcmentioning
confidence: 99%
See 1 more Smart Citation
“…This hypothesis probably explains the higher MAEWS-BrC-365 values obtained during late night and morning time except afternoon, which recorded the greatest solar flux (Figure 1b). During afternoon time, a recent study 25 suggested that photochemical oxidation can cause concurrent oxygenation (bleaching) of existing BrC chromophores and formation of nitrogen containing BrC chromophores. Our observations during afternoon are supportive to this hypothesis that WS-BrC bleaching dominates any absorption enhancement whatsoever due to formation of nitrogen containing chromophores during afternoon resulting overall decrease in MAEWS-BrC-365.…”
Section: Diurnal Variability Of Ws-brcmentioning
confidence: 99%
“…The extent of these processes vary temporally and spatially. 10,25,26 Several previous studies have explored the diurnal [25][26][27][28] and spatial 5,29 variation in sources and absorptivity values of BrC globally. However, field evidence on the role of various atmospheric processes, temperature and RH in governing diurnal variation of chemical composition and absorptivity values of BrC are sparse, especially over Indo-Gangetic Plain (IGP).…”
Section: Introductionmentioning
confidence: 99%